Study of Block Chain Technology and its Applications - Prudhviraj, Kambala; Venkataramana, K (International Journal of Computer Sciences and Engineering, 2025)
In the future most of market deals with the Blockchain Technology, because this technology has decentralized database that records the data such as finance contracts, physical assets, and supply chain information. It has achievement over the time and is currently dominated and used by Bitcoin. It is not a new technology but it shown up with the bitcoin, now a days some of the transactions are done with the cryptocurrency. It gives innovative solutions for FinTech Industry. This technology has energized the financial services industry globally. This concept already brought a disruption in the financial industry. Coming the some of the Industries, which already implementing this technology are, Deutsche Bank, DBS Bank, EBA (Euro Banking Association), US Federal Reserve are some of Financial Sector Banks are going to use this Technology in as like Digital Payments, Assets. This technology is Transparent Business way. So this is very secured and transparent. It is like as distributed ledger.